BGP-15 Protects against Heart Failure by Enhanced Mitochondrial Biogenesis and Decreased Fibrotic Remodelling in Spontaneously Hypertensive Rats. (30th January 2021) - Horvath, Orsolya; Ordog, Katalin; Bruszt, Kitti; Deres, Laszlo; Gallyas, Ferenc; Sumegi, Balazs; Toth, Kalman; Halmosi, Robert
Abstract : Heart failure (HF) is a complex clinical syndrome with poor clinical outcomes despite the growing number of therapeutic approaches. It is characterized by interstitial fibrosis, cardiomyocyte hypertrophy, activation of various intracellular signalling pathways, and damage of the mitochondrial network. Mitochondria are responsible for supplying the energy demand of cardiomyocytes; therefore, the damage of the mitochondrial network causes cellular dysfunction and finally leads to cell death. BGP-15, a hydroxylamine derivative, is an insulin-sensitizer molecule and has a wide range of cytoprotective effects in animal as well as in human studies. Our recent work was aimed at examining the effects of BGP-15 in a chronic hypertension-induced heart failure model. 15-month-old male SHRs were used in our experiment. The SHR-Baseline group represented the starting point (n = 7 ). Animals received BGP-15 (SHR-B, n = 7 ) or placebo (SHR-C, n = 7 ) for 18 weeks. WKY rats were used as age-matched normotensive controls (n = 7 ). The heart function was monitored by echocardiography. Histological preparations were made from cardiac tissue. The levels of signalling proteins were determined by Western blot. At the end of the study, systolic and diastolic cardiac function was preserved in the BGP-treated animals. BGP-15 decreased the interstitial collagen deposition via decreasing the activity of TGF β /Smad signalling factors and prevented the cardiomyocyte hypertrophy in hypertensive animals. BGP-15 enhanced the prosurvival signalling pathways (Akt/Gsk3 β ). The treatment increased the activity of MKP1 and decreased the activity of p38 and JNK signalling routes. The mitochondrial mass of cardiomyocytes was also increased in BGP-15-treated SHR animals due to the activation of mitochondrial biogenesis. The mitigation of remodelling processes and the preserved systolic cardiac function in hypertension-induced heart failure can be a result—at least partly—of the enhanced mitochondrial biogenesis caused by BGP-15.